Molecular Mechanisms of Breast Cancer Drug Resistance and CRISPR/Cas9 Strategies to Overcome - Bashdar Mahmud Hussen; Bnar Saleh Ismael; Saman S. Abdulla; Noor Haval Jamal; Suhad Asad Mustafa; Zana Baqi Najmalddin; Mohammed Fatih Rasul (BioMed Target Journal)
Breast cancer (BC) is considered as the most frequent cancer among women and a significant contributor to mortality. The CRISPR/Cas9 gene-editing tool has promising applications for BC drug resistance. It is a unique and creative approach that has lately attracted attention and can be used to fix gene alterations related to multidrug resistance. Recent research has effectively investigated and targeted particular genes linked to BC treatment resistance using CRISPR/Cas9 gene editing, including those linked to hormone receptor signaling, drug efflux transporters, and DNA repair pathways. The CRISPR/Cas9 technology's selective disruption or mutation of these genes provides valuable information about their role in resistance and paves the path for cutting-edge treatment options. CRISPR/Cas9 gene editing can overcome BC treatment resistance by identifying crucial genetic variables and revealing new therapeutic targets Despite the advantages, there are limitations in the study on CRISPR/Cas9-based gene editing for BC treatment resistance, for example, off-target effects and the improvement of delivery techniques are still major issues. Successful clinical translation depends on methods to improve the specificity and effectiveness of CRISPR/Cas9 editing and to solve these constraints. This review aims to explore the possibility of CRISPR/Cas9 gene editing as an innovative method of combating BC medication resistance.